Analisis Determinan Harga Saham Bris (Pt Bank Syariah Indonesia Tbk) - Latifah, Latifah; Pasaribu, Rifdah Atika; Pulungan, Rahmat Rizki; Harahap, Muhammad Ikhsan (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This research is to analyze the efffect of liquidity ratios, profitability, bi rate, consumer price index and the money supply on BRIS stock prices. The method used in this research is descriptive quantitative method. In this study there are six variables consisting of five independent variables and one dependent variable. The independent variables in this study are the ratio of liquidity, profitability, bi rate, consumer price index and the money supply while the dependent variable is stock prices. Method analysis used multiple regression analysis. The results of this study indicate that ROA, BI rate, and money supply (JUB) partially affect BRIS stock prices with their respective significance levels, namely ROA of 0.0251, BI rate of 0.0000, Money in circulation of 0.0000. Meanwhile , the Current Ratio (CR) and Consumer Price Index (CPI) variables have no effect on BRIS stock prices. Based on this, it can be concluded that the independent variables jointly affect the BRIS stock price.